(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Amanda Gorman speaks through the language of paradox in her poem "The Miracle of Morning”. Her artistic expression, appealing voice and the aesthetic of the language of paradox instill hope and a sense of community building in people to survive the unprecedented crisis of Covid-19. She captures the hopeless mood of the American people battered by the unknown disease and attempts to soothe the bereaved hearts and minds who are mourning the unexpected loss of lives and are living under the unknown fear of the pandemic. To discuss the aesthetics and effectiveness of the language of paradox, this paper uses Cleanth Brooks’ theory of poetry. His concept of the language of poetry as the language of paradox supports the analyses of the imagery and paradoxes in the poem drawn from day to day lives and familiar activities. This paper argues that such language enables the readers to perceive the ordinary or the commonplace differently, positively and hopefully, and helps them realize the profound truth of the complexes of human lives. Gorman fills the crisis-ridden people with positivity, hope and unity to overcome the unknown fear as a common human crisis. The high production of poetry during the Pandemic approves the power of poetry and its language to heal the deeper wounds and give company in moments of separation and loneliness that people had to bear while keeping with the social and physical distancing. Poetic imagination steers the readers to in-depth truth that lies beyond the explicitly paradoxical situations that ordinary minds fail to perceive.